Lung tumors on multimodal radiographs derived from grating-based X-ray imaging - A feasibility study - Meinel, Felix G.; Schwab, Felix; Yaroshenko, Andre; Velroyen, Astrid; Bech, Martin; Hellbach, Katharina; Fuchs, Jeanette; Stiewe, Thorsten; Yildirim, Ali Oe; Bamberg, Fabian; Reiser, Maximilian F.; Pfeiffer, Franz; et al. (Physica Medica, 2014)
Purpose: The purpose of this study was to assess whether grating-based X-ray imaging may have a role in imaging of pulmonary nodules on radiographs. Materials and methods: A mouse lung containing multiple lung tumors was imaged using a small-animal scanner with a conventional X-ray source and a grating interferometer for phase-contrast imaging. We qualitatively compared the signal characteristics of lung nodules on transmission, dark-field and phase-contrast images. Furthermore, we quantitatively compared signal characteristics of lung tumors and the adjacent lung tissue and calculated the corresponding contrast-to-noise ratios. Results: Of the 5 tumors visualized on the transmission image, 3/5 tumors were clearly visualized and 1 tumor was faintly visualized in the dark-field image as areas of decreased small angle scattering. In the phase-contrast images, 3/5 tumors were clearly visualized, while the remaining 2 tumors were faintly visualized by the phase-shift occurring at their edges. No additional tumors were visualized in either the dark-field or phase-contrast images. Compared to the adjacent lung tissue, lung tumors were characterized by a significant decrease in transmission signal (median 0.86 vs. 0.91, p=0.04) and increase in dark-field signal (median 0.71 vs. 0.65, p=0.04). Median contrast-to-noise ratios for the visualization of lung nodules were 4.4 for transmission images and 1.7 for dark-field images (p=0.04). Conclusion: Lung nodules can be visualized on all three radiograph modalities derived from grating-based X-ray imaging. However, our initial data suggest that grating-based multimodal X-ray imaging does not increase the sensitivity of chest radiographs for the detection of lung nodules. © 2013 Associazione Italiana di Fisica Medica.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Chest radiography; Lung tumors; X-ray dark-field imaging; X-ray phase-contrast imaging